A CONSIDERATION OF THE MATERIALS FOR TEACHING PAST TENSES IN ENGLISH GRAMMAR COURSE BOOKS - El Fadl, Saber Abou (PEOPLE: International Journal of Social Sciences, 2021)
The study examines 30 grammar course books to find out how past tense lessons are organised, and what kind of approaches are adopted by materials’ developers to design them for the different targeted learners (Beginners to advanced). Various pedagogical frameworks for the design of teaching materials are reviewed, in the light of SLA research findings related to the acquisition of grammar. To examine the constructs of past tenses in the selected sample of course books, the methodology adopted in this research draws on mix-methods and case study (quantitative and qualitative analyses) for the purpose of ensuring validity. Data was collected using checklists that aim to account for the different components used by material developers to teach past tenses including form, meaning and activities. The findings reveal a strong implication of internal and external factors of L2 acquisition in the process of designing past tenses materials. Finally, the results indicate an interesting trend about the different uses of grammar activities according to learners’ language proficiency level. In this way, the findings of the present research seem to contradict the previous studies that claim the unique use of controlling activities by materials developers.